2016
DOI: 10.1021/acsami.5b12025
|View full text |Cite
|
Sign up to set email alerts
|

Microscopy Study of Structural Evolution in Epitaxial LiCoO2 Positive Electrode Films during Electrochemical Cycling

Abstract: The evolution of interface between the epitaxial thin film LiCoO2 (LCO) electrode and liquid electrolyte and inside the LCO film during electrochemical cycling has been analyzed by high resolution scanning transmission electron microscopy. Relaxation of sharp translational domain boundaries with mismatched layers of CoO2 octahedra occurs during cycling and results in formation of continuous CoO2 layers across the boundaries. The original trigonal layered structure of LiCoO2 tends to change into a spinel struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 46 publications
3
60
0
Order By: Relevance
“…This contributes to promote the charge and discharge electrochemical cycles when this compound is used as a cathode in lithium-ion batteries. 10,[71][72][73] The densities of states, in Figure 9, show a contribution predominance of the oxygen p orbitals and cobalt d orbitals in the HOMO/LUMO frontier orbitals and small contribution of the hybridization between these orbitals.The analyses by SEM (Figure 10) show the morphology, texture and habit of the HT-LiCoO 2 synthesized with the starch and gelatin precursors and in the blank test. We also present the SEM analyses using the citric acid and glycine precursors in Figure S7 (Supplementary Information).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This contributes to promote the charge and discharge electrochemical cycles when this compound is used as a cathode in lithium-ion batteries. 10,[71][72][73] The densities of states, in Figure 9, show a contribution predominance of the oxygen p orbitals and cobalt d orbitals in the HOMO/LUMO frontier orbitals and small contribution of the hybridization between these orbitals.The analyses by SEM (Figure 10) show the morphology, texture and habit of the HT-LiCoO 2 synthesized with the starch and gelatin precursors and in the blank test. We also present the SEM analyses using the citric acid and glycine precursors in Figure S7 (Supplementary Information).…”
mentioning
confidence: 99%
“…This contributes to promote the charge and discharge electrochemical cycles when this compound is used as a cathode in lithium-ion batteries. 10,[71][72][73] The densities of states, in Figure 9, show a contribution predominance of the oxygen p orbitals and cobalt d orbitals in the HOMO/LUMO frontier orbitals and small contribution of the hybridization between these orbitals.…”
mentioning
confidence: 99%
“…By comparing with the spectra of the standard transition metal oxide compounds, it is revealed that the average valence states of the Co, Mn, and Ti ions in the as‐synthesized NCMT‐2 are 2+, 3.7+, and 4+. It is very surprising that Co ions can be stabilized at 2+ in the P2‐type layer‐structured compounds, since the valence state of Co ions in most layer‐structured cathode materials is 3+ 12, 23, 39. In addition, the valence state of Mn ions in NCMT‐2 is 3.7+, which is higher than Mn 3+ in tunnel‐structured Na 0.66 Mn 0.66 Ti 0.34 O 2 18.…”
Section: Resultsmentioning
confidence: 99%
“…This basis becomes evident as we examine results from our previously (or yet to be published) reports on cathode materials that cover a range of chemistries and phases [12][13][14][15]. The underlying feature, namely the oxygen sublattice, is identified as the commonality between these different crystallographic phases, and the one that facilitates the observed epitaxial growth.…”
Section: Introductionmentioning
confidence: 94%
“…Pulsed laser deposition (PLD) is a well-established method that is suitable for producing high-quality dense oxide films without post-deposition annealing. Several research groups have utilized PLD to deposit and study different epitaxial cathode films, such as layered LiCoO 2 [7][8][9][10][11][12][13][14], different Li-Mn-O structures [15][16][17][18][19], and compositionally complex Li-TM-O (TM = Co, Mn, Ni) [20][21][22][23][24]. In our previous work, we demonstrated that robust electrochemical measurements (cyclic voltammetry and impedance spectroscopy) can be performed on such binder-free films by utilizing SrRuO 3 (SRO)-Epitaxially deposited on single-crystal SrTiO 3 (STO) substrates-As a conductive electrode [12]; with this approach, it has been shown that different stages of cycling can be studied by atomic resolution scanning TEM (STEM) [13].…”
Section: Introductionmentioning
confidence: 99%